Influence of varying carbon content in (V, Nb, Ta, Ti, W)C high entropy carbide - Ni based cermets on densification, microstructure, mechanical properties and phase stability. Issue 3 (1st February 2023) - Anwer, Zahid; Vleugels, Jozef; Datye, Amit; Zhang, Shuhan; Huang, Shuigen
Abstract: The influence of varying carbon content on the microstructure and mechanical properties was studied in the (V, Nb, Ta, Ti, W)C - 12 vol% Ni system, allowing to define the carbon window for eta and graphite phase formation. Microstructure and phase analysis were performed by scanning electron microscopy (SEM), X-ray diffraction (XRD) and electron probe microanalysis (EPMA), and the transverse rupture strength (TRS), Vickers hardness and Palmqvist fracture toughness were measured. The results elucidate the influence of the carbon content on the eutectic temperature, carbide grain size and morphology, phase stability and mechanical properties in high entropy carbide (V, Nb, Ta, Ti, W)C-Ni cermets. The phase stability and chemical reactivity with steel of the High Entropy Carbide (HEC) cermets was assessed in static interaction couples at 1200°C, and compared with that of a conventional WC-Co cemented carbide.